The Problem of overtaking the basic design of the city of Baghdad (alternative and Solutions) - Hamoudi Hassan, Hatem (International Journal of Psychosocial Rehabilitation, 2020)
The problem of overcoming the basic design of the city of Baghdad after a year, 2003, is the problem of the times; the research aims to determine if treating it and adapting it through the civil study questionnaire, which is prepared to district the city of Baghdad. The overrun represents the public property of the state and individuals, mostly written and surveyed community services, and road and river taboos. The research determined the research problem is a weakness in planning decisions, the security aspect, economic, social, and housing problems, and the absence of awareness among the population exacerbated the problem and multiple questions. The research may consist of the three topics, as the first topic dealt with the theoretical framework and the second topic covered basic designs for the city of Baghdad and the role of planners, laws, and legislation to reduce the phenomenon of overtaking. The third topic covered the field study of overtaking, alternatives, and solutions, and the research concluded with the most critical result. The overtaking came due to the poor urban management of the city and the absence of the rule of law, which led to environmental, visual, and the comfort of the community. As for the critical proposal in activity solutions and alternative, the comprehensive development project proposals for the year 2030 by the urban planning department and the municipalities of districts, the city of Baghdad, to reduce the phenomenon of overtaking.